An eight-step change model - McArdle, Geri E. H.
Is your organization planning a large-scale change initiative? Do you know what needs to be done to manage and facilitate this process smoothly? And just as important, do you know how to alleviate the fears of those going through this process? Change can be messy, scary, and challenging. But with the right process, tools, and facilitation efforts in place, it can be a smooth and positive experience.